DENTAL CARIES IN CHILDREN AGED 6-12 YEARS USING THE "HI BOGI" APPLICATION IN CIMAHI ELEMENTARY SCHOOL IN 2021 - Putri Noer Fadilah, Rina; Hartman, Henri; Putra Kusaeri, Ramadhani (Journal of Health and Dental Sciences, 2024)
Caries are a dental and oral problem that most often occurs in elementary school-age children. The emergence of the COVID-19 pandemic has caused most dental examinations and treatments to be postponed, and only emergency dental procedures can be performed with teledentistry, one of which is the HI BOGI application has to prevent, educate or detect early dental and oral problems. This study aims to find out the description of caries in children aged 6-12 years using the "HI BOGI" application at Cimahi City Elementary School in 2021. The research subjects were 315 children obtained by cluster random sampling method. This research is descriptive and observational. According to WHO, the indicators and standards for measuring the severity of dental caries are the DMF-T index for assessing permanent teeth and the DMF-T index for primary teeth. The DMF-T/dmf-t (Decay Missing Filled Teeth) index is a value that indicates the severity of tooth decay due to caries. The results showed that from the DMF-T/dmf-t examination on 315 children, the results of the DMF-T and DMF-T index status results were the average value of the DMF-T index of 0.746 including the very low criteria and the average value of the dmf-t index was obtained of 1.39 is included in the low criteria. Based on the area of ​​Cimahi City District, the DMF-T index in the North District (0.327) and Central (0.482) is very low. South District (1.582) is included as low, and for DMF index status in North (2) and Central District (1.254) including low and South District (0.835) is included as very low. In conclusion, the caries status of children aged 6-12 years at SD Kota Cimahi in 2021 is in the low-status category for primary teeth and very low for permanent teeth. DOI : 10.54052/jhds.v3n3.p227-238